2014
DOI: 10.3389/fgene.2014.00348
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rainbow trout spleen transcriptome and identification of immune-related genes

Abstract: Resistance against diseases affects profitability of rainbow trout. Limited information is available about functions and mechanisms of teleost immune pathways. Immunogenomics provides powerful tools to determine disease resistance genes/gene pathways and develop genetic markers for genomic selection. RNA-Seq sequencing of the rainbow trout spleen yielded 93,532,200 reads (100 bp). High quality reads were assembled into 43,047 contigs. 26,333 (61.17%) of the contigs had hits to the NR protein database and 7024 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 116 publications
3
19
1
Order By: Relevance
“…Moreover, 66 of those Siluriformes entries were from a single species, the American channel catfish ( Ictalurus punctatus ). These results contrast with other published transcriptome analysis of fish species that used BLASTX against the NCBI Non-redundant (Nr) database, reflecting the underrepresentation of Siluriformes sequences on more well curated databases (Ali et al, 2014; Zhenzhen et al, 2014). …”
Section: Resultscontrasting
confidence: 87%
“…Moreover, 66 of those Siluriformes entries were from a single species, the American channel catfish ( Ictalurus punctatus ). These results contrast with other published transcriptome analysis of fish species that used BLASTX against the NCBI Non-redundant (Nr) database, reflecting the underrepresentation of Siluriformes sequences on more well curated databases (Ali et al, 2014; Zhenzhen et al, 2014). …”
Section: Resultscontrasting
confidence: 87%
“…As for genes of the IFN receptor genes, IFNR1 and IFNR2 were expressed in both the TO-VS-IFN/SAV3 and TO-VS-SAV3 suggesting that activation of IFN-α/β receptors occurs as consequence of infection as well as IFN I treatment (as would be expected). However, it is important to point out that although our findings show the presence of both IFNR1 and IFNR2, which is in agreement with observations made by Ali et al [44] who reported the presence of both IFNR1 and IFNR2 based on a transcriptome analysis of rainbow trout spleen. Studies carried out by Sun et al [45] suggest that Atlantic salmon possess two clusters type I IFN receptor genes located on different chromosomes which allow for a large repertoire of IFN receptors than mammals and zebrafish.…”
Section: Kegg Pathway Analysissupporting
confidence: 94%
“…In teleost fish, spleen is an important secondary immune organ, related to innate and adaptive immunity, erythrocyte turnover and hemoglobin recycling (Ali et al, 2014). Environmental factors, such as temperature, constitute a strong adaptive trigger and are suspected to have left specific signatures in the immune response of animals inhabiting distinct regions (Windisch et al, 2012).…”
Section: Short Introductionmentioning
confidence: 99%